Comparison of Putative Phytochemicals in Endophytic Fungi of Frangipani (Plumeria rubra) - Kaur, Arshpreet (Thapar University, Patiala, 2016)
Frangipani (Plumaria sp.) is commonly known ornamental and medicinal plant. The bioactives of this plant possess anticancer, antitumor, antifouling and cosmeceutical properties thus making it a prime subject of research. However, endophytic fungi, an endosymbiont are known to mimic the properties of host plant and produce similar bioactive compounds like that of host plant. Hence, the focus of the present study was to compare the bioactive constituents of endophytic fungi of Frangipani plant with its own phytochemicals. In the present study, 33 endophytic fungi were isolated from leaves of Frangipani (Plumaria rubra) collected from different locations of Patiala. All the endophytic fungi were subjected to culture filtrate production followed by extraction with ethyl acetate. Subsequently, secondary metabolites were also isolated from leaves of frangipani plant so as to compare its bioactive compound profiling with crude EA fraction of endophytic fungi. The EA fractions of all endophytic fungi were compared with crude leaf fraction of Frangipani by using preparative thin layer chromatography (TLC). Out of 33 cultures, only #88FPLPR was showing three bands with identical Rf value to that of plant fraction. Further, crude EA fraction of #88FPLPR and plant fraction was analysed by HPLC. On comparing the HPLC chromatogram, two peaks were found to be similar in both fractions at same retention time of 2 min and 5.3 min. For further confirmation of presence of identical compounds were deduced from GC-MS analysis. In GC-MS data, 7 compounds of crude EA fraction of #88FPLPR were found to be similar to crude plant fraction which shows the presence of 21 compounds in total. The potential isolate was identified as Nigrospora sp through classical taxonomy while sequencing data of ITS region is awaited till now. Further speciation of #88FPLPR would be done after analyzing sequencing data. However, the results of the present study were providing preliminary data about the ability of endophyte to mimic the properties of host plant for validation of this hypothesis.
Keywords: Phytochemicals; Phytochemicals; Endophytic Fungi; Nigrospora Plumeria; Bioactive Compounds